Styles of coping in a stressful situation, social support and psychological consequences in emigrants from the Netherlands - Bujek-Kubas, Iwona; Kopczyński, Przemysław; Mojs, Ewa (Journal of Medical Science, 2020)
Emigration is an experience irrevocably associated with stress caused by leaving one’s family home, changing one’s social environment as well as living conditions, etc. The main aim of this study was to establish if and what correlations there are between different styles of coping with stress, social support and psychological consequences resulting from the emigration of a group of 96 Polish emigrants living in the Netherlands. The participants were clients of the Pomoc Nederland (the name reflects the company’s objective to help the Poles living in the Netherlands) company, aged from 31 to 50 years and they had lived abroad for 1 to 20 years. The research tools applied in the study included the Social Support Questionnaire and the Inventory to Measure Coping Strategies with Stress Mini-COPE. The psychological consequences of emigration-related stress were evaluated using: the Scale of Positive and Negative Experience (SPANE), the State-Trait Anxiety Inventory (STAI) and the Satisfaction with Life Scale (SWLS). The findings showed that in the group of subjects, certain personal resources were significantly correlated with constructive strategies of coping with stress while living abroad. It was revealed that among the evaluated emigrants only emotional support was significantly correlated with certain psychological consequences resulting from emigration-related stress.
Keywords: emigration; stress; the Netherlands; styles of coping; social support